2019
DOI: 10.1111/jne.12682
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific contribution of DHEA‐cortisol ratio to prefrontal‐hippocampal structural development, cognitive abilities and personality traits

Abstract: Although dehydroepiandrosterone (DHEA) may exert neuroprotective effects in the developing brain, prolonged or excessive elevations in cortisol may exert neurotoxic effects. The ratio between DHEA and cortisol (DC ratio) has been linked to internalising and externalising disorders, as well as cognitive performance, supporting the clinical relevance of this hormonal ratio during development. However, the brain mechanisms by which these effects may be mediated have not yet been identified.Furthermore, although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…Further, the indirect effects of TC ratio on cognition through structural covariance only affect spatial span, not shifting abilities. Interestingly, we have also shown sex-specific associations between ACC-hippocampal covariance and the ratio between dehydroepiandrosterone (DHEA) and cortisol, 15 as well as cognitive benefits of DHEA:cortisol ratio in both boys and girls. 43 In comparison with estradiol -a metabolite of testosterone, DHEA is a precursor hormone for testosterone, i.e.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Further, the indirect effects of TC ratio on cognition through structural covariance only affect spatial span, not shifting abilities. Interestingly, we have also shown sex-specific associations between ACC-hippocampal covariance and the ratio between dehydroepiandrosterone (DHEA) and cortisol, 15 as well as cognitive benefits of DHEA:cortisol ratio in both boys and girls. 43 In comparison with estradiol -a metabolite of testosterone, DHEA is a precursor hormone for testosterone, i.e.…”
Section: Discussionmentioning
confidence: 79%
“…54 These results provide further evidence that the polymorphic effects of testosterone on cognition are composed of both direct (activation of androgen receptors and effects on cortico-hippocampal development) and indirect effects (conversion to estradiol, activation of estradiol receptors, and effects on cortico-amydalar development). 12,15,43,54 We also document sex-specific contributions of TC ratio to prefrontal-hippocampal development. However, sex differences in brain structure as a function of TC ratio did not result in sex differences in cognition in our study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…I suggested that the primary effect (among others) of increasing DHEAS is the maintenance of plasticity in the developing brain (36,37), a point since elaborated by others (38,39). Recent finding showing an impact of DHEA on cortical development and cortical-limbic connectivity in children (14)(15)(16)(40)(41)(42)(43) provide strong support for this argument.…”
Section: Introductionmentioning
confidence: 90%
“…To be convincing arguments about the evolution of unique human traits like mentalizing (148) or the emergence of a novel life stage like middle childhood (55) require both a physiological substrate and evidence for a phylogenetic precursor. The onset of DHEAS production during early childhood (119,120), and its impact on brain development during both early and middle childhood (14,42,43), together with the emergence of mentalizing from 9 to 11 years (147) fits both criteria. Adrenarche is a physiological process with neurological consequences related to behaviors during middle childhood, and the increase in DHEAS is linked to the development of the adrenal ZR.…”
Section: Human Evolution Weaning and Meatmentioning
confidence: 99%